Dualities of Function: Archaeological Approaches to the Study of Movement and Space within the late‒Victorian Department Store - Kate Morris (Cahiers Victoriens et Edouardiens)
Department stores, in the second half of the nineteenth century, can be characterised as spaces with multiple functional identities. Retailers aimed to maximise potential sales through a combination of innovative display, modernised architecture, and the curation of customers’ movement, which promoted increased sales opportunities by assistants. In large stores, where sales figures were the only indicator of success, assistants were under pressure to ‘never allow a lady to leave without a sale’. Women, however, were inclined to view department stores as leisure spaces, respectable enough to be visited without an escort. This duality of function, with department store interiors existing simultaneously as sales floor and leisure space, appears to have resulted in tension between sales staff and customers. Drawing on the extensive literature focused on spatial archaeologies of eighteenth-century retail interiors, this article considers the department store as an extension of earlier shopping practice, drawing links between the private pseudo-domestic parlours of the Georgian shop and the refreshment rooms of the department store. It is shown that the creation of subdivided interiors allowed for the separation of retail and leisure space, allowing for the easing of tension between staff and customer, and demonstrating a continuation of the retail owner as peer and host for the customer.